Case report: Autoimmune glial fibrillary acidic protein astrocytopathy with overlapping autoimmune syndrome - Wei, Wu-xiao; Chen, Ming-li; Meng, Lian (Frontiers in Immunology, 2024)
Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is a rare autoimmune disease, which is characterized by the immune system attacking astrocytes in the central nervous system, resulting in inflammation and damage to the nervous system. We reported a 41-year-old female patient with only drowsiness for three months, who was otherwise healthy with no other signs of meningoencephalitis or myelitis. There were no obvious abnormalities in her neurological and ophthalmic tests. Brain magnetic resonance imaging (MRI) plain scan + enhancement with the gadolinium contrast agent revealed patchy hypointensity on T1WI, hyperintensity on T2WI, hyperintensity on T2-FLAIR in the left basal ganglia, corona radiata, and local septum pellucida, with no enhancement in the enhanced lesions. Cerebrospinal fluid (CSF) revealed white blood cell count 5.00 ×10 6 /L, CSF protein 828.53 mg/L, and glucose 2.83 mmol/L. Aquaporin-4 antibody, NMDA receptor antibody and GFAP antibody were all positive, whereas the remaining autoimmune encephalitis antibody tests were negative. Oncology screening (including head, chest, whole abdomen (involving the pelvic cavity) CT and tumor markers) did not reveal any obvious evidence of tumor presence. The patient received systemic treatment with high-dose intravenous injection of steroids combined with immunosuppressive agents, and the clinical and imaging features of the patients improved. To the best of our knowledge, reports on overlapping positivity of aquaporin-4 antibody (AQP4) and N-methyl-D-aspartate receptor (NMDAR) antibody in patients with GFAP astrocytopathy were still very rare.We hope to supplement the existing literature on this topic, review the relevant literature, and strive to increase the understanding toward GFAP astrocytopathy with overlapping autoimmune syndrome, so as to enable early diagnosis and early treatment, and improve the clinical outcome of patients.